For all x, (3x + 1)² = ?
A.) 6x + 2 B.) 9x² + 1 C.) 9x² + 3x + 1 D.) 3x² + 1 E.) 9x² + 6x + 1
(3x + 1)²
= (3x + 1)(3x + 1) {when squaring a binomial, multiply it by itself} = 3x(3x) + 3x(1) + 1(3x) + 1(1) {used foil method} = 9x² + 3x + 3x+ 1 {multiplied through} = 9x² + 6x + 1 {combined like terms}E.)- Algebra House
0 Comments
Your comment will be posted after it is approved.
## Leave a Reply. |
Latest Videos## Archives
June 2021
ACT is a registered trademark of ACT, Inc. SAT is a registered trademark of the College Board. ACT and SAT are not affiliated with this site. |